High salt diet alleviates disease severity in native experimental autoimmune uveitis - Derluyn, Naomi; Foucart, Vincent; Verce, Marko; Abdo, Rami; Vaudoisey, Louis; Lipski, Deborah; Flamand, Véronique; Everard, Amandine; Bruyns, Catherine; Willermain, François (Frontiers in Ophthalmology, 2024)
BackgroundRecent studies reported a link between high salt diet (HSD) and clinical exacerbation in mouse models of autoimmune diseases, mainly through the induction of pathogenic Th17 cells and/or HSD-induced dysbiosis. However, the topic remains controversial and not fully understood.PurposeIn this study, we investigated the effects of HSD on the development of experimental autoimmune uveitis (EAU) in C57BL/6J mice.Methods and resultsUnexpectedly, our data showed a significant attenuating effect of HSD on disease severity of native EAU, induced by direct immunization with IRBP peptide. That said, HSD had no effect on EAU disease severity induced by adoptive transfer of semi-purified auto-reactive IRBP-specific T lymphocytes. Accordingly, HSD did not affect IRBP-specific systemic afferent immune response as attested by no HSD-linked changes in T lymphocytes proliferation, cytokine production and Treg proportion. Gut microbiota analysis from cecal samples in naïve and EAU mice demonstrated that HSD affected differentially α-diversity between groups, whereas β-diversity was significantly modified in all groups. Unknown Tannerellaceae was the only taxon associated to HSD exposure in all treatment groups. Interestingly, a significantly higher abundance of unknown Gastranaerophilales, with potential anti-inflammatory properties, appeared in HSD-fed native EAU mice, only.DiscussionIn conclusion, our study suggests a possible impact of HSD on gut microbiota composition and consequently on development and clinical severity of EAU. Further studies are required to investigate the potential beneficial role of Gastranaerophilales in EAU.